Integration of Business Strategy and Human Resource Planning at BAZNAS (Badan Amal Zakat Nasional) of West Nusa Tenggara Province: A Knowledge-Performance Analysis to Enhance Zakat Fund Management Performance - Iin Santika Agustini; Nia Supiani; Pena Riadien; Santi Nururly (Postgraduate University of Mataram, 2026)
Modern organizational management models position human resources as the strategic element that determines the success of institutional direction and objective implementation. The classical assumption that organizational performance improvement relies solely on formal structure and systems is no longer adequate to explain the complexity of zakat management in the digital era. The integration of Human Resource Planning, Strategic Human Resource Management, and Knowledge Management provides a more comprehensive framework for understanding the relationship among competency, performance, and institutional strategy effectiveness. In the context of BAZNAS (Badan Amal Zakat Nasional) of West Nusa Tenggara Province, changes in the external environment, demands for public transparency, and the acceleration of digitalization affirm the importance of strengthening HR capacity through knowledge–performance mapping, talent development based on strategic needs, and optimization of institutional knowledge. Zakat digitalization programs, mustahik empowerment innovations, and cross-sectoral collaboration demonstrate that HR quality directly impacts the success of organizational transformation. Adaptive HR planning, structured knowledge management, and aligned organizational strategy create a strong foundation for enhancing institutional accountability, operational efficiency, and social impact.